On Legalizing Physician-Assisted Death for Dementia - Dresser, Rebecca (The Hastings Center report, 2017)
Last November, soon after Colorado became the latest state to authorize physician-assisted suicide, National Public Radio's The Diane Rehm Show devoted a segment to legalization of “physician assistance in dying,” a label that refers to both physician-assisted suicide and voluntary active euthanasia. Although the segment initially focused on PAD in the context of terminal illness in general, it wasn't long before PAD's potential application to dementia patients came up. A caller said that her mother had Alzheimer's disease and was being cared for at great expense. Suspecting that she will suffer the same fate, the caller reported that she had included in her will “my specific request that if I should be diagnosed, and it is legal to do so, I would like to opt out of a life and many years of suffering.” A few countries, such as the Netherlands and Belgium, already allow PAD for dementia in certain circumstances. It wouldn't be surprising to see a U.S. legalization effort in the coming years.